Pamagra Bali Learning Media with a Gamification Approach to Increase Interest in Learning Balinese - I Wayan Sindu Yamuna; I Nyoman Laba Jayanta; Made Vina Arie Paramita (Universitas Pendidikan Ganesha, 2025)
The low interest of students in learning Balinese script material is a challenge in efforts to preserve the regional language and culture in elementary schools. This study aims to analyse the PAMAGRA BALI learning media using a gamification approach to increase elementary school students' interest in learning Balinese. This research is a research and development (R&D) study with a one-group pretest-posttest design, following the ADDIE model. The research subjects included two material experts, two media experts, one teacher-practitioner, and 19 fourth-grade students as trial subjects. The data collection method used questionnaires, interviews, and learning interest questionnaires, with instruments in the form of expert validation sheets, teacher and student response sheets, and learning interest rating scales. Data analysis was carried out using descriptive statistics to assess validity and practicality, and inferential statistics through prerequisite and hypothesis tests to assess the effectiveness of the media. The results showed that the PAMAGRA BALI media met the criteria for being very valid and very practical and were effective in increasing students' learning interest. Thus, the development of concrete media based on gamification can be an innovative solution in overcoming the low interest in learning Balinese while supporting more active and meaningful learning. The implications of this research indicate that integrating manipulative media and gamification can serve as a contextual learning strategy to strengthen local cultural literacy in elementary schools.